1990
DOI: 10.1007/bf00032407
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soybean planting density on dinitrogen fixation and yield

Abstract: We investigated the effect of planting density on soybean (Glycine max (L.) Merr.) yield in glasshouse and field experiments. Because net canopy photosynthesis increases with increasing plant density, we hypothesized that increasing planting density would result in increasing rates of dinitrogen fixation in soybeans and higher yields per unit land area.In glasshouse studies, Wayne variety soybeans were planted in 10-cm diameter pots, 1 plant pot-1 in matrices of 10-, 15-, 20-, 25-, or 30-cm equidistant interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Nodule dry weight was not correlated with plant biomass, or with the N accumulated at V4, but was significantly correlated at R5 (both with p < 0.0001) (data not shown), indicating that increased nodule mass in low-density treatments was related to higher rates of nitrogen fixation. In contrast, Kapustka and Wilson (1990) found that an increase in soybean plant density reduced nodule number and dry weight per plant, but maintained high specific activity per nodule, which resulted in the same values of nitrogen fixation per plant.…”
Section: Discussionmentioning
confidence: 76%
“…Nodule dry weight was not correlated with plant biomass, or with the N accumulated at V4, but was significantly correlated at R5 (both with p < 0.0001) (data not shown), indicating that increased nodule mass in low-density treatments was related to higher rates of nitrogen fixation. In contrast, Kapustka and Wilson (1990) found that an increase in soybean plant density reduced nodule number and dry weight per plant, but maintained high specific activity per nodule, which resulted in the same values of nitrogen fixation per plant.…”
Section: Discussionmentioning
confidence: 76%
“…They stated that, at lower plant densities the photosynthetic rate per plant increased and, consequently, higher carbon (C) supplied to the nodules resulted in an increase in nodulation and in nitrogen fixation rates. Kapustka and Wilson (1990) also found out that, an increase in soybean plant density reduced nodule number. The lower nodule per plant for local variety interaction with row spacing in compare with nasir and goberesha interaction with all tested row spacing might be from nature of the variety.…”
Section: Resultsmentioning
confidence: 85%
“…In other instances, however, as population increased, the number of branches per plant (Blumenthal et al 2005), yield per plant (Ball et al 2000), pod and seed number per plant, and seed weight per plant (Boquet 1990) decreased. Population or Row spacing also influenced lodging, weed resurgence and N fixation (Herbert and Litchfield 1984, Kapustka and Wilson 1990, Yelverton and Coble 1991, Blumenthal et al 2005; weed resurgence increased as Row spacing increased (Yelverton and Coble 1991).…”
Section: Introductionmentioning
confidence: 99%